2009
DOI: 10.3945/jn.108.096511
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Genotyping the 677C>T Variant of Methylenetetrahydrofolate Reductase in Humans Is Decreased in the Post-Folic Acid Fortification Era

Abstract: Moderate hyperhomocysteinemia is associated with many diseases. Major factors affecting plasma total homocysteine (tHcy) concentrations include folate concentrations and polymorphisms in the methylenetetrahydrofolate reductase (MTHFR) gene. Because U.S.-mandated fortification of grain products with folic acid has improved folate and tHcy status in Americans, we investigated the effect of the MTHFR 677C>T variant before and after fortification. We determined tHcy and folate concentrations in sera from 844 Cauca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…In the current study we are able to compare the association of polymorphisms in the CBS, MS, MTRR and MTHFR genes with tHcy concentrations before and after folic acid fortification. We have previously shown in a smaller subset of CARDIA that folic acid fortification was associated with increased concentrations of folate and decreased prevalence of moderate hyperhomocysteinemia [31], similar to results from the Framingham and the National Health and Nutrition Examination Survey (NHANES) studies [29, 30]. In this study, we also examined how folic acid fortification influenced the association of the MTHFR 677C>T polymorphism with tHcy concentrations.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the current study we are able to compare the association of polymorphisms in the CBS, MS, MTRR and MTHFR genes with tHcy concentrations before and after folic acid fortification. We have previously shown in a smaller subset of CARDIA that folic acid fortification was associated with increased concentrations of folate and decreased prevalence of moderate hyperhomocysteinemia [31], similar to results from the Framingham and the National Health and Nutrition Examination Survey (NHANES) studies [29, 30]. In this study, we also examined how folic acid fortification influenced the association of the MTHFR 677C>T polymorphism with tHcy concentrations.…”
Section: Discussionsupporting
confidence: 53%
“…As a result, studies have shown that folate status has significantly improved with a concurrent decrease in prevalence of moderate hyperhomocysteinemia [29, 30]. Our group, in a previous study of a subset of 844 Caucasian and 587 African American participants of the Coronary Artery Risk Development in Young Adults (CARDIA) study showed that homozygosity of the MTHFR 677T allele plays a less significant role in predisposing the United States population to moderate hyperhomocysteinemia in the post folic acid fortification era [31]. Although polygenic regulation of tHcy has been examined in populations with premature CAD or at high risk for CAD [2,32], there are no studies investigating the effect of multiple homocysteine metabolizing genes on the level of tHcy after folic acid fortification in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…59 This public health initiative may be incidentally reducing some of the perceived risk associated with MTHFR polymorphisms. 60,61 This is hypothesized to be one reason that an association between the "thermolabile" variant and venous thromboembolism is no longer observed in the North-American population. 21 The American Congress of Obstetricians and Gynecologists does not recommend the measurement of homocysteine or MTHFR polymorphisms in the evaluation of the etiology of venous thromboembolism.…”
Section: Acmg Practice Guidelinesmentioning
confidence: 99%
“…The geographic differences might indicate that the influence of the TT genotype is dependent on folate status, because the folate intake increased substantially in North American countries after January 1998, when folic acid fortification was introduced (43). After that time, the average serum folate concentration increased by 2-fold, the average homocysteine concentration fell significantly among the general population (44), and the difference in the homocysteine concentration by the MTHFR C677T genotype was significantly attenuated (45). However, we cannot rule out the possibility that the temporal association between when the inverse association of CVD mortality and MTHFR TT genotype began to become apparent and when mandatory folate fortification was implemented in the United States was merely coincidental.…”
Section: Discussionmentioning
confidence: 85%